Jubiläums-Katalog 1919-1969. - Galerie Aenne Abels, Köln (Köln : Galerie Aenne Abels, 1969)
Altmann, Adolf ; Barlach, Ernst ; Blumenthal, Hermann ; Barrera Bossi, Erma ; Eberts, Josef ; Gilles, Werner ; Gosekuhl, Rudolf ; Guérin, A.M. ; Heckendorf, Franz ; Hoelzel, Adolf ; Hofer, Carl ; von Jawlensky, Alexej ; Kandoldt, Alexander ; Klein, César ; Klopotan, Franjo ; Kolbe, Georg ; Alvarez Laverón, Elena ; Lehmbruck, Wilhelm ; Lichtner-Aix, Werner ; Macke, August ; Marc, Franz ; Mataré, Ewald ; etc.
Jubiläums-Katalog 1919-1969, Galerie Aenne Abels, Köln, 1969
boek